Ethical case studies for advanced practice nurses : solving dilemmas in everyday practice - Vermeesch, Amber; Cox, Patricia H.; Giske, Inga M.; Roberts, Katherine M. (Indianapolis, IN : Sigma, 2023)
'Healthcare delivery can present ethical conflicts and dilemmas for advanced practice registered nurses (APRNs)--nurses who already have a myriad of responsibilities in caring for patients. Ethical Case Studies for Advanced Practice Nurses improves APRNs' agility to resolve ethical quandaries encountered in primary care, hospital-based, higher education, and administration beyond community settings. Through case studies examining various types of ethical conflicts, the authors empower APRNs and students with the critical knowledge and skills they need to handle even the most complex dilemmas in their practice. By applying a set of criteria and framework, this book guides APRNs to use critical thinking to make ethically sound decisions. Case study topics include: substance use in pregnancy, elder-care issues, depression screening in adolescents, abortion and moral values, medical emancipation versus confidentiality in transgender and gender-nonconforming people, prescription refills for patients with financial hardship'--Cover.
Defensive medicine -- STI confidentiality -- Substance use in pregnancy -- HPV vaccine refusal -- Abortion -- Prostate cancer screening with prostate-specific antigen -- Administration of long-acting injectable antipsychotics -- Depression screening in adolescents -- Treatment of resistant anxiety -- COVID-19 vaccine in adolescence -- Medical emancipation versus confidentiality in transgender and gender-nonconforming people -- Childhood obesity -- Dementia and stopping driving -- When to transition to palliative care -- Prescription refill dilemma for patient and spouse in financial straits -- CRNA labor and delivery epidural pain management with a language barrier -- Violence, suicide, and family dynamics with medical complexity -- Psychiatric acute concerns and fall risks -- Telehealth -- Guiding a school of nursing through COVID-19 focusing on clinical placements -- Emergency department closure decision-making: health system and community impact -- Ethical dilemmas in school of nursing leadership pre-COVID-19.
Includes bibliographical references and index.
WorldCat record variable field(s) change: 050
Keywords: Nursing -- Study and teaching -- United States -- Case studies; Nursing ethics -- United States -- Case studies; Nursing ethics; Nursing -- Study and teaching; United States; Case studies